Actual problems of development of information legislation - Кукшина, Ольга Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The paper analyzes trends in the national information laws around the world. Certain general features ofits formation.